Vibrations - Balachandran, Balakumar (Thomson Brooks/Cole, 2004)
Covering linear and non-linear single degree-of-freedom and multi-degree-of-freedom systems, this book teaches the use of vibration principles. The authors present vibration principles in a general context and illustrate the use of these principles through examples from different disciplines.